Generating real context data to test user dependent systems - application to multi-agent systems - Oliveira, Pedro Filipe (2020)
This paper, deals with the usually need of data to simulate behavior and efficiency of proposed solutions in several fields, and also knowing that personal data always bring privacy and security issues. This work wants to promote a balanced solution between the need of personal information and the user’s privacy expectations. We propose a solution to overcome these issues, and don’t compromise the balance between security and personal comfort based on generating real context data of users, that allow to test user dependent systems.